Reflections of glory : Paul's polemical use of the Moses-Doxa tradition in 2 Corinthians 3.1-18 /: Paul's polemical use of the Moses-Doxa tradition in 2 Corinthians 3.1-18. (2015) - Belleville, Linda L
No abstract available